Characterization of Coating Flour Based on Local Timor Corn Flour Modified with the Addition of Rice Flour, Tapioca Flour, and Glutinous Rice Flour - Maria Susana Medho; Aydamel Asisaul Gelora Mentur Takalapeta; Endeyani Vivitrida Muhamad; Yosefina Lewar (The University of Lampung, 2025)
The application of pure corn flour (100%) as coating material tends to generate a tough texture, thus requiring an alternative formulation to obtain a crispier result. This research aimed to evaluate the physical, chemical, and sensory characteristics, as well as to determine the optimal coating flour composition. The study was carried out using nine formulations, consisting of varying proportions (%) of corn flour, rice flour combined with tapioca flour, and glutinous rice flour. Formulas involved A (60:35:5), B (60:30:10), C (60:25:15), D (50:45:5), E (50:40:10), F (50:35:15), G (40:55:5), H (40:50:10), and I (40:45:15). The findings indicated that incorporating rice flour, tapioca and glutinous rice to the coating flour significantly affected the physical and chemical properties. The proportion of corn flour 50% by adding rice flour and tapioca 35%, glutinous rice flour 15% gave a higher panelist preference value for crispiness, which was 4.36. Glutinous rice flour was able to change the proportion of amylose and amylopectin so that the texture was crispy and not too hard when the product was cooled. The characteristics of the coating flour included viscosity value of 3.29mP, WHC 152.89%, OHC 107.53%, protein 4.50%, starch 69.41%, amylose 18.47%, and amylopectin 50.94%.